UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT BUAH LANGSAT (Lansium domesticum Cor.) TERHADAP Shigella flexneri - ., Fransiska Sepdahlia (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Diarrhea remains a health problem in developingcountries such as Indonesia. Poor environmental sanitation and thelack of clean water sources lead to this disease. Diarrhea can besevere when it becomes bloody diarrhea, which can be calleddysentery. Langsat (Lansium domesticum Cor.), one of the speciesfrom Meliaceae family, is a tropical plant in Indonesia. Studies ofliterature, concerning the empirical data, show that part of langsatcan be used to treat diarrhea and bloody diarrhea. Objective: Thisresearch aimed to determine the antibacterial activity of the ethanolextract of langsat peel (Lansium domesticum Cor.) against Shigellaflexneri, the content of the compound and the minimum inhibitoryconcentration (MIC) of ethanol extract of langsat peel.Methodology: Langsat peel was extracted by maceration using96% ethanol. The extracts obtained carried out phytochemicalscreening test. the antibacterial activity test carried out with KirbyBauerDisc Difussion methods against Shigella flexneri.Ciprofloxacin 5 g/ disc was used as positive control while 96%ethanol was used as negative control. Results: Based on thephytochemical screening test, ethanol extract of langsat peelcontains phenols, flavonoids, tannins, saponins, triterpenoids andalkaloids. This research showed no minimum inhibitoryconcentration (MIC) of ethanol extract of langsat peel that can beused against Shigella flexneri. Conclusion: The ethanol extract oflangsat peel has no antibacterial activity against Shigella flexneri.Keyword: Antibacterial, ethanol extract of langsat peel, Shigellaflexneri1) Medical School, Faculty of Medicine, University of TanjungpuraPontianak, West Borneo.2) Pharmacy School, Faculty of Medicine, University ofTanjungpura Pontianak, West Borneo.3) Medical School, Faculty of Medicine, University of TanjungpuraPontianak, West Borneo.